ARTIFICIAL INTELLIGENCE AND THE FUTURE OF FOREIGN LANGUAGE EDUCATION: OPPORTUNITIES, CHALLENGES, AND ETHICAL QUESTIONS - M.B. Mirzaraimova (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This article investigates the theoretical and pedagogical foundations of integrating Artificial Intelligence (AI) into foreign language education. The article argues that AI represents a logical extension of linguistic thought rather than a radical break from it, translating human semiotic and communicative principles into algorithmic forms. By tracing the historical evolution of linguistic paradigms, this article identifies how structuralism, functionalism, communicative competence, and multimodality collectively inform contemporary AI pedagogy. It concludes that while AI provides unprecedented opportunities for personalization, intercultural engagement, and multimodal learning, it simultaneously raises profound ethical and epistemological questions about authenticity, meaning, and the human role in language acquisition.